PENGARUH PEMBERIAN AROMATERAPI LEMON TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA 1 FASE AKTIF PADA IBU PRIMIGRAVIDA DI BIDAN PRAKTEK MANDIRI (BPM) WILAYAH KERJA PUSKESMAS BATU AJI - Lesawengen, Monisye; Utami, Risqi (Universitas Batam, 2019)
Background Lemon oil Aromatherapy can improve mood, relax the mind, increase concentration, overcome pain and anxiety. Linalool, one of the substances contained in lemon, is useful to stabilize the nervous system so that it can cause a calm effect for anyone who inhales it. The purpose of this study was to find out the effects of lemon aromatherapy on the reduction of labor pain intensity of primigravida mothers active phase I This research methodapplied posttest only control group design, conducted at BPM, Puskesmas Batu Aji Work Area on February-July 2018 with a total population of 3872 pregnant women and a sample of 60 respondents, sampling applied Accidental Sampling with a sample of 30 experimental groups and 30 control groups. Data was analyzed using test analysis techniquesT-Test. The results of the study found that the mean reduction in pain intensity in the control group 1.60 ± 0.498 and in the experimental group 0.50 ± 0.509 from 30 respondents in the control group and 30 experimental groups experienced a decrease in pain 1.1, then the results of the T-Test test p-value value 0,000 (p <0,05). The conclusionof this study there is the effect of lemon aromatherapy on reducing the intensity of labor pain. Suggestions Respondents are expected to apply aromatherapyfor maternal mother and community as an alternative treatment for people who experience labor pain.